Imperative Sentences for The Mangompoi Jabu Ceremony for The Toba Batak Ethnic: Study of Speech Actions - Rajagukguk, Try Putra (Institute of Computer Science (IOCS), 2019)
Imperative sentences found in the Toba Batak regional language can range from very loud or harsh orders to very subtle or polite requests. Imperative sentences can also range from being told to do something to being prohibited from doing something. Thus it can be said that the imperative sentence in the Toba Batak is complex and varied. Based on the formulation of the problem, this study aims to determine the use of the imperative sentence of the Mangompoi Jabu ceremony of the Batak Toba ethnic group: Tutur action study and to describe, classify functions and also interpret imperative sentences at the Mangompoi Jabu ceremony, Batak Toba ethnicity: Tutur action study. This study used descriptive qualitative method. Data analysis was carried out by means of data analysis techniques, namely, observing the whole text of the conversation of the Mangompoi Jabu ceremony for the Toba Batak ethnic group, classifying the data, analyzing the conversation text carefully. The results of the study found that: (1) All imperative sentence forms, namely: ordinary imperative, request imperative, permit granting imperative, invitation imperative, and order imperative are in the Toba Batak ethnic Mangompoi Jabu ceremonial sentence (2) Of the seventeen imperative sentence forms, There were fourteen imperative pragmatic forms used, namely: the pragmatic form which means command; pragmatic form means orders; pragmatic form means request; pragmatic form means request; pragmatic form means persuasion; pragmatic form means appeal; pragmatic form means tolerance; pragmatic form means invitation; pragmatic form means to permit; pragmatic form means prohibition; pragmatic form means hope; pragmatic form of permit requests; pragmatic form means to permit; pragmatic form means prohibition; pragmatic form means hope; pragmatic form means recommendation. Meanwhile, the four other imperative pragmatic forms are: the pragmatic form means pressure; the pragmatic form of swearing; and pragmatic form means ngelulu, not found.